Answer:
20>4
Step-by-step explanation:
12-3 forget about the x 12-3=9 . 9+11=20
(17-9)=8 . 8-4 =4
so your answer is correct
Answer:
X₁=7 ,X₂ = 5
Step-by-step explanation:
a= 1² b= - 12 c= 35
X =[ ( -b±√b²-4ac ) / 2a]
So, use this formula and get the answer...
Even if you use the middle term formula, you will get the same answer
Answer: the answer is $ 17,349.21 APEX
Answer:
c>6, since a negative coefficient reverses the sign
Step-by-step explanation:
7-c<1
-c<-6
c>6
Answer:
-81
Step-by-step explanation:
-6(2x² + 5x) - 9
substitute -4 for 'x'
-6[2(-4)² + 5(-4)] - 9
-6[2(16) + (-20) - 9]
-6(32 - 20) - 9
-6(12) - 9
-72 - 9 = -81